Eutrema tianshanense (Brassicaceae), a new species from Tian Shan Mountains of central Asia - Hao, Guoqian; Al-Shehbaz, Ihsan A.; Liang, Qianlong; Wang, Qian; Liu, Jianquan (Phytotaxa, 2016)
Eutrema tianshanense, a new species of Brassicaceae growing near to the permanent glaciation area in the Tian Shan Mountains of central Asia, is described. It is quite similar morphologically to E. heterophyllum, and E. racemosum from the Qinghai-Tibet Plateau and adjacent regions, and to E. edwardsii of Qinghai-Tibet Plateau, Central and North Asia, and northern North America, but with rounder and smaller leaves. In addition to its long-distance disjunction from the ranges of the above three species, phylogenetic analyses based on sequence variations of multiple chloroplast DNA markers and nuclear ITS suggested that E. tianshanense and these species represent two independently evolved lineages in Tian Shan Mountains and the Qinghai-Tibet Plateau. Their morphological similarities may have resulted from the same selection pressures in the alpine habitats where they grow.